2021
DOI: 10.1177/10986111211009048
|View full text |Cite
|
Sign up to set email alerts
|

Women and Policing: An Assessment of Factors Related to the Likelihood of Pursuing a Career as a Police Officer

Abstract: Law enforcement is still considered a male dominated occupation resulting in the underrepresentation of women in sworn personnel positions. While it is critical for police departments to have a more representative police force, there is a lack of research on the factors that affect the likelihood of women entering policing. Past studies suggest that men and women have similar reasons for joining policing. However, research on the factors that deter potential candidates from pursuing this career path is limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The nature of policing has historically excluded women from its ranks mainly due to perceptions of policing as stressful, dangerous, physically demanding, and a sexist occupation (Diaz and Nuño, 2021). The literature review identifies two major themes surrounding the nature of police work, as described below.…”
Section: Socio-cultural Perceptions Of the Nature Of Police Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of policing has historically excluded women from its ranks mainly due to perceptions of policing as stressful, dangerous, physically demanding, and a sexist occupation (Diaz and Nuño, 2021). The literature review identifies two major themes surrounding the nature of police work, as described below.…”
Section: Socio-cultural Perceptions Of the Nature Of Police Workmentioning
confidence: 99%
“…According to different authors, policing is a male-dominated profession that perpetuates the wrong idea that women do not belong on the force and the efforts to gain equality within policing are often unsuccessful (Diaz and Nuño, 2021). Situations of inequity, on the other hand, may be related to the different assimilation strategies followed by police institutions (Heidensohn, 1998).…”
Section: Organizational Structure and The Police Subculture: Cultural Manifestations In Police Institutions And Discriminationmentioning
confidence: 99%
“…Therefore, policing is often held out as a male-dominated field, one of the most 1 The University of the West Indies, St Augustine, Trinidad and Tobago masculinised occupations of the world (Chan & Ho, 2013;Chen, 2015;Diaz & Nuño, 2021;Mukherjee, 2018;Randhawa & Narang, 2013;Veldman et al, 2017) as well as a male preserve (Archbold & Schulz, 2012;Punnoose, 2013). The maleness of policing is highlighted in research findings by Kringen (2014) and Status of Women (2014) which identified that globally, women represent about 13% of all individuals in policing and by Brown et al (2020) and Diaz and Nuño (2021) who cogitate that females continue to be underrepresented in policing. The result of this 'hegemonic masculinity' in policing (Deans, 2015;Shelley et al, 2011) is that there is a preponderance of males over females in police services globally (Aquino, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Policing emerged in the 19th century as a male only occupation (Carrington et al, 2019). Therefore, policing is often held out as a male-dominated field, one of the most masculinised occupations of the world (Chan & Ho, 2013; Chen, 2015; Diaz & Nuño, 2021; Mukherjee, 2018; Randhawa & Narang, 2013; Veldman et al, 2017) as well as a male preserve (Archbold & Schulz, 2012; Punnoose, 2013). The maleness of policing is highlighted in research findings by Kringen (2014) and Status of Women (2014) which identified that globally, women represent about 13% of all individuals in policing and by Brown et al (2020) and Diaz and Nuño (2021) who cogitate that females continue to be underrepresented in policing.…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature has identified some possible reasons for these issues (i.e. that the profession is unattractive to women; gendered organizational culture and policies); however, the question of why representation is so low for women officers across all spaces in law enforcement is still not well understood (Cordner and Cordner, 2011; Diaz and Nuno, 2021; Franklin, 2005; Kringen, 2014).…”
mentioning
confidence: 99%